Le Front populaire dans les récits historiques pour la jeunesse - Patricia Richard-Principalli (Amnis)
While the social and international current events highlight the process of destruction of the gains and hopes that 1936 inaugurated, the commemoration of the 80th anniversary of the Popular Front (1936-2016) resulted, quite timidly, in a number of manifestations and appearances, which were not relayed in the media. Similarly, literature for adults has scarcely taken hold of the Popular Front for this anniversary, although this year's commemoration has not given rise to any publication in youth literature. This relative discretion in the commemoration of the 80th anniversary of the Popular Front is thus a weak memory transmission, which this study seeks to observe how it is reflected in the construction of the privileged collective memory that constitutes the youth literature. It is a question of understanding the place, quantitative and qualitative, of the Popular Front among historical narratives for youth, to analyze their writing strategies and their stakes, in order to understand what transmission is here at work. The study is based on a corpus of 6 publications (1996-2013).